Penjadwalan Mata Kuliah Dengan Perampingan Algoritma Evolusi Dan Pembobotan Distribusi Beban Kuliah - Adi Chandra Syarif; Farif Hartono Gunawan (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2014)
Course scheduling problem belongs to the category of NP - hard (Non - deterministic polynomial - time complex). The complexity of solving course scheduling problems give an indication to the limits of the constraintsto the problem. This research focusses on the development of applicable course scheduling program at University of Atma Jaya Makassar. The problem with the previous scheduling program can not be implemented to prodcecourse schedule because there are some additional factors that affect the scheduling process at the University of Atma Jaya Makassar. The development was done by adjusting the scheduling process currently used to program scheduling course. The end result of this research is a scheduling program course at the University of Atma Jaya Makassar to overcome certain problems lecture schedule and can distribute the load of the course each semester in one week.